CLUSTER ANALYSIS APPLICATION IN THE EVALUATION OF THE FOREIGN ECONOMIC POTENTIAL OF UKRAINE`S REGIONS - Luzhanska, N. O.; Lebid, I. H.; Kravchenya, I. M. (Systems and Technologies, 2020)
To analyze the market situation and to determine the demand for services provided by freight customs complexes in the regions of Ukraine, it is proposed the application of statistical data analysis methods for a comprehensive regional foreign economic potential assessment. The observation objects were twenty-four regions of Ukraine and the city of Kyiv in the period from 2015 to 2018. A number of indicators reflecting the level of their development were used as regional foreign economic potential assessment factors. As a research tool, such statistical analysis methods as hierarchical cluster analysis techniques and the k-meansmethod in Statistica, the suite of analytics software products, are used. Following the classification results, the regions of Ukraine are divided into five homogeneous clusters based on which it is possible to develop a system of differentiated measures for each cluster of regions with the high, average, and low levels of foreign economic activity development.